ANALISA PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL (STUDI KASUS PADA GURU SMP NEGERI 19 KERINCI) - Ferry Siswadhi; Rian Martias (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2019)
This study aims to determine and analyze whether there is influence of motivation and work discipline on the performance of teachers of SMP Negeri 19 Kerinci. This research is categorized as associative causal research of quantitative approach with questionnaire instrument. The population in this study is all teachers of SMP Negeri 19 Kerinci as many as 30 people. Sampling technique by means of saturated sampling technique or census. The sample in this study is by taking the population or as many as 30 samples. The data used in this study are primary data obtained through questionnaires and secondary data obtained by relevant agencies and journals to support this research. Instrument validity test using Correclation Bivariate formula, while reliability test using Cronbach Alpha. Measurers proved to be valid and reliable for research instruments. Multiple regression analysis is used to test the hypothesis of this research. The results showed that: Motivation (X1) has a positive and significant effect on the performance of teachers of SMP Negeri 19 Kerinci (β) 0.461. with significance of 0.004. Work discipline (X2) has a positive and significant effect on the performance of Teacher of SMP Negeri 19 Kerinci (β) 0,684 with significance equal to 0.000. And based on the test results of the two independent variables tested individually the most dominant in influencing the performance of Teachers SMP Negeri 19 Kerinci is the discipline of work (with coefficient 0.684). Then it can be concluded that in this study work discipline (X2) is a partial factor that significantly affect Performance (Y).